ILLOCUTIONARY ACTS PERFORMED BY THE MAIN CHARACTER IN THE MATRIX MOVIE - Nainggolan, Olleta Vichi; Arifin, M. Bahri; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
ABSTRACTThe aims of this research were to find out the illocutionary acts performed by the main character in The Matrix movie and to identify the context underlying the illocutionary acts in the main character’s utterances. This research used Searle’s classification of illocutionary acts and Hasan and Halliday’s theory of context. There were 3 steps that applied on this research. The first was to select the utterances spoken by Neo as the main character in The Matrix movie which contain illocutionary acts and categorized them; then identified the context. The second step was to present the findings by using descriptive method. The last step was to draw the conclusion. There were four types of illocutionary acts found in the utterances spoken by Neo. The data were classified into representatives (24), directives (82), commissives (2), and expressives (5). However, the declaratives types of illocutionary acts were not found in the main character’s utterances because Neo had no power or authority to change the reality with his words in The Matrix movie. From the findings, directives were the dominant type of illocutionary acts in the main character’s utterances because he repeatedly expressed his utterances in direct way by questioning, ordering, begging and asking. The context of the utterances is described by identifying the field, tenor and mode of each utterance spoken by the main character in the movie.Key words: Speech Act, Illocutionary Acts, Utterance, Context